The first lesson in the classroom – getting students engaged in active learning process - Eva Langkilde, Annette (Improving University Science Teaching and Learning, 2023)
The aim of this project was to search for alternative ways of encouraging the students to take an active part in the classroom, and to break from the traditional walk-through of exercises on the blackboard. The focus in this report is on the initiatives made for the first session, as I believe the impressions from the first encounter have a crucial impact on the rest of the course programme. If the students walk away from the first session with a good “feeling” of being capable, and at the same time getting something out of showing up and participating, the positive attitude will affect the following lessons.